PENGEMBANGAN MEDIA DIORAMA PEMBELAJARAN “BUMIRA” MISTERI PERUT BUMI BERBANTUAN AUGMENTED REALITY (AR) PADA MATERI LAPISAN-LAPISAN BUMI KELAS 5 SEKOLAH DASAR - Fiki Kristiani; Kukuh Andri Aka; Kharisma Eka Putri (Jurnal Manajemen Pendidikan, 2026)
This study aimed to develop the BUMIRA “Mystery of the Earth's Interior” learning media assisted by Augmented Reality (AR) for the Earth Layers topic in fifth-grade elementary school and to analyze the validity, practicality, and effectiveness of the developed media. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 29 fifth-grade students at SD Negeri Sukorame 2, with a limited trial involving 6 students and a field trial involving 23 students. Data were collected through observations, interviews, expert validation, response questionnaires, and learning achievement tests. The results showed that the BUMIRA learning media achieved an overall validity score of 91%, consisting of 88% from the media expert and 95% from the subject matter expert. The media also obtained a practicality score of 94%, based on a teacher response score of 96%, a limited-trial student response score of 92%, and a field-trial student response score of 95%. In addition, the media achieved an effectiveness score of 91%, as indicated by the percentage of students who achieved classical learning mastery in the field trial. The novelty of this study lies in the integration of a three-dimensional diorama with Augmented Reality technology in the BUMIRA learning media, enabling abstract concepts of the Earth's layers to be presented in a more concrete, interactive, and meaningful way for elementary school students.